(untitled) (Research Journal Tahqeeqat, 2025)
Saeed Ashar’s short story collection Nofishing is a significant and nuanced contribution to the tradition of Urdu fiction. This article presents a cultural analysis of the collection, exploring how the author weaves themes of changing social attitudes, class disparities, urban-rural contrasts, and the conflict between tradition and modernity into his narratives. The characters, dialogues, and settings in Nofishing vividly reflect the internal and external dimensions of South Asian particularly Pakistani culture. This study delves into the cultural layers, local color, symbolism, and metaphorical language present in the stories, aiming to interpret the collection not only as a literary work but also as a cultural document. Ultimately, the article argues that Saeed Ashar’s storytelling offers a compelling and meaningful reflection of contemporary cultural realities within the broader context of Urdu literature.